The Impact of Specialized Training in the Development of Skilled Performance to Prepare From Above the Head Volleyball for the Establishment of the Specialized School - Hasan, Bahaa Kasib Abbas (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the research is to prepare volleyball training for the school’s specialized children as well as to know the impact of special training in the development of the skilled performance of the preparation of above the head with volleyball for young people, for specialized trainings a moral effect in the skilled performance of preparation from above the head to the school’s juniors Specialist.The researcher used the experimental method by designing (one group) with Pre and posttests to suit the nature of the research, and the researcher identified the research community represented by the players of the specialized school in Baghdad IV, which numbered 47 players and the research sample was selected from the research community in a random way With 12 juniors, the percentage of the main sample is (25.53%) This is an appropriate proportion of real and honest representation of the research community, as well as the selection of (8) players who represented the sample of the survey experience.